Probing the nature and reactivity of coordination complexes with blended organic and inorganic chromophores using vibrational spectroscopy - Horvath, Raphael; Huff, Gregory S.; Gordon, Keith C.; George, Michael W. (Elsevier, 2016)
The use of transient vibrational spectroscopy in the analysis of rhenium(I) and ruthenium(II) complexes is discussed. Particular focus is given to the use resonance Raman spectroscopy to probe initial photoexcitation and transient resonance Raman and infrared spectroscopy to observe subsequent relaxation processes. The utility of these techniques is given by discussion of examples in which the electronic complexity of the system increases from systems which are nominally pure metal-to-ligand charge-transfer through to systems which have complex interplay between intraligand and metal-to-ligand charge transfer states. The use of these later systems in dye-sensitised solar cells is also briefly discussed.